Cutting-edge dielectric nanofluids: a review of factors influencing stability and thermo-dielectric properties - Farade, Rizwan A.; Abdul Wahab, Noor Izzri; Rafiq, Muhammad; Shah, Nehad Ali; Khan, T. M.Yunus; Ghori, Syed Waheedullah (Springer Science and Business Media, 2025)
Dielectric nanofluids (DNFs) exhibit extraordinary potential in sustainability efforts, as they pave the way for the advancement of compact transformers and heat transfer equipment. This is primarily attributed to their remarkable capacity to augment the thermo-dielectric performance. Numerous factors exert a profound influence on the performance of dielectric nanofluids. Hence, these factors hold paramount significance. Many existing review articles lacking in comprehensive, multifactor perspective. This leads to fragmented insights and difficulty in comparing studies. Existing studies lack real-world relevance, and there is a disconnect between experimental results and industrial settings. This article critically analyzes multiple factors in a single, unified article. Offers deeper insights into the underlying surface mechanisms by empirical support. Provides a comprehensive analysis of the practical implications, challenges in practical applications, and future research directions. In this context, extensively incorporated cutting-edge literature encompasses both commercial and noncommercial grade transformer fluids and heat transfer oils, as well as single-constituent, hybrid, composite, and doped nanoparticles. The encompassed studies indicate that these factors significantly influence the stability and thermo-dielectric properties of dielectric nanofluids. The average AC breakdown voltage (BDV) enhancement was approximately 35%, thermal conductivity improved by around 26%, and tan δ was reduced by about 33%. This article serves as a valuable resource to address challenges and optimize the performance of DNFs focused on energy-efficient transformers and heat transfer equipment, bridges experimental findings with industrial applications, and highlights future research directions.